Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1175/jcli-d-11-00100.1
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Climatology of Southern Hemisphere Mobile Fronts in a Modern Reanalysis

Abstract: Presented here is an objective approach to identify, characterize, and track Southern Hemisphere mobile fronts in hemispheric analyses of relatively modest resolution, such as reanalyses. Among the principles in its design were that it should be based on broadscale synoptic considerations and be as simple and easily understood as possible. The resulting Eulerian scheme has been applied to the European Centre for Medium-Range Weather Forecasts (ECMWF) Re-Analysis (ERA)–Interim and a climatology of frontal chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
128
0
14

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(151 citation statements)
references
References 82 publications
4
128
0
14
Order By: Relevance
“…Fronts are associated with strong winds and increased fire danger (Mills 2005). Recent climatologies indicate the prevalence of fronts as rain bearing systems, particularly cold fronts, across southern Australia (Berry et al 2011, Simmonds et al 2012. Any trends in observed winds are difficult to establish due to sparse coverage of wind observations, difficulties with instruments and the changing circumstances of anemometer sites (Jakob 2010).…”
Section: Mean Meridional Circulation and The Subtropical Ridgementioning
confidence: 99%
“…Fronts are associated with strong winds and increased fire danger (Mills 2005). Recent climatologies indicate the prevalence of fronts as rain bearing systems, particularly cold fronts, across southern Australia (Berry et al 2011, Simmonds et al 2012. Any trends in observed winds are difficult to establish due to sparse coverage of wind observations, difficulties with instruments and the changing circumstances of anemometer sites (Jakob 2010).…”
Section: Mean Meridional Circulation and The Subtropical Ridgementioning
confidence: 99%
“…4e,f and 4g,h), consistent with the need for the moderate background baroclinicity that serves to discriminate between these pathways. This baroclinicity may arise from one of several sources: subtropical atmospheric fronts (Todd and Washington 1999) such as those that are uniformly present in the Southern Hemisphere summer at 308S (Simmonds et al 2012), precursor baroclinic vortices (Davis and Bosart 2002), or meridional SST gradients that exist poleward of the equatorial SST maxima (Reynolds et al 2002).…”
Section: Pathway Climatologymentioning
confidence: 99%
“…Frontal systems are very important for rainfall in southern Australia (Berry et al, 2011;Simmonds et al, 2012) particularly in the southeast in autumn (Catto et al, 2012) and the southwest in winter, where they have been found to be declining in number (Hope et al, 2014). Fronts in an example GCM, ACCESS1.3, tend to be well represented in their frequency and the proportion of precipitation associated with them (Catto et al, 2013), although the intensity of that precipitation is underestimated.…”
Section: Introductionmentioning
confidence: 99%